The art and architecture of thailand : from prehistoric times through the thirteenth century - Woodward, Hiram ([S.l.] : Brill Academic Publishers, 2005)
Written sources on Thai history are scarce. It took Hiram Woodward many years of painstaking archaeological and art-historical research to finally piece together this first ever comprehensive survey work on the art and architecture of Thailand from the earliest times until the establishment of the Thai-speaking kingdoms. The book, organized geographically and chronologically, covers four eras: the prehistoric period; the period characterized by the culture of the kingdom of Dvaravati; the centuries of Khmer dominance; and, as classical Khmer civilization waned, the period of the struggle for identity. A systematic and elucidating history of pre-fourteenth-century Thailand in a volume indispensable to historians of art, religion, politics, and society.
Keywords: Architecture; Art, Thai; Thailand